Mapping care provision for type 1 diabetes throughout Australia: a protocol for a mixed-method study - Jeffrey Braithwaite; Yvonne Zurynski; Jennifer Couper; Sophia Zoungas; Timothy Jones; Elizabeth Davis; David Bloom; Ann Carrigan; Rebecca Lake; Tony Huynh (BMJ Open, 2022)
Introduction Type 1 diabetes (T1D) is a chronic and incurable autoimmune disease, diagnosed in early childhood and managed initially in paediatric healthcare services. In many countries, including Australia, national audit data suggest that management and care of T1D, and consequently glycaemic control, are consistently poor. This can lead to adverse outcomes such as cardiovascular disease and nephropathy. T1D treatment is complex, multidisciplinary, multiagency and life-long and should involve patient-centred, developmentally appropriate care. Although an emerging body of literature describes T1D models of care, their components, implementation determinants and associated outcomes are poorly understood.Objectives To provide a study protocol to describe methods to map existing models of care for children and young adults living with T1D. It will identify the gaps and needs in care delivery as viewed by healthcare providers and by children, young people and their families accessing care in metropolitan and rural or remote regions throughout Australia.Methods and analysis A mixed-method study that includes provider and consumer-specific surveys and interviews about current T1D care provisions. Data will be analysed thematically (qualitative) and statistically (quantitative) and synthesised to describe the key characteristics of effective and sustainable models of care for T1D and to identify gaps.Ethics and dissemination Ethics approval was granted by the Macquarie University Human Research Ethics Committee in July 2022 (#520221154439676). Results will be disseminated via publication in peer-reviewed journals and at relevant conferences.